Exploring the Status of Self-Regulated Strategies and Self-Efficacy Beliefs in Learning English Grammar among Iranian EFL Learners - Omid Mallahi (Iranian Journal of Educational Research)
Objective: The present study investigated the relationship between self-regulation strategy use and self-efficacy beliefs in learning English grammar and grammatical knowledge of a group of Iranian EFL learners. Methods: The study adopted a correlational design and the data were collected by using a set of questionnaires. Results: The results of data analyses indicated that these constructs are positively correlated. The results of multiple regression also showed the significance of managing environment and behavior strategy in accounting for the grammatical knowledge of the learners. Furthermore, the MANOVA results proved the superiority of more proficient students in their self-regulation and self-efficacy beliefs. Conclusions: Finally, it was suggested that learners' cognitive understanding of grammar is interconnected with their beliefs about their capabilities and their strategic use of learning methods. Therefore, educators should design language courses that integrate both grammar instruction and strategies to enhance learners' self-regulation and self-efficacy levels.